2003
DOI: 10.1017/s1472928803000104
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric thalamocortical dysrhythmia: surgical implications

Abstract: Neuropsychiatric surgery has had a long and complex history with examples of less than optimal surgical procedures implemented in wrong settings. Such past errors have raised important philosophical and ethical issues that remain with us for good reasons. However, the existence of enormous suffering due to chronic therapy-resistant disabling neuropsychiatric disorders compels a search for alternative surgical approaches based on a sound understanding of the underlying physiopathological mechanisms. We bring ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 19 publications
1
24
0
4
Order By: Relevance
“…These results, using the average signal of many EEG electrodes from schizotypal individuals, resemble the results reported using the average signal of many MEG sensors from clinical SZ individuals Jeanmonod et al, 2003;Llinas and Ribary, 2001;Llinás et al, 2001;Llinas et al, 1999;Sarnthein et al, 2003) and the interpretation is that there exists a slight, but widespread, perturbation of thalamocortical resonance (TCD) in individuals who exhibit the cluster of personality traits associated with schizotypy.…”
Section: Power Spectra Cross-correlationsupporting
confidence: 75%
See 3 more Smart Citations
“…These results, using the average signal of many EEG electrodes from schizotypal individuals, resemble the results reported using the average signal of many MEG sensors from clinical SZ individuals Jeanmonod et al, 2003;Llinas and Ribary, 2001;Llinás et al, 2001;Llinas et al, 1999;Sarnthein et al, 2003) and the interpretation is that there exists a slight, but widespread, perturbation of thalamocortical resonance (TCD) in individuals who exhibit the cluster of personality traits associated with schizotypy.…”
Section: Power Spectra Cross-correlationsupporting
confidence: 75%
“…In particular, our group of HiS individuals 1) locked the thalamocortical loop in the low-α band at a lower-frequency oscillation, as measured with individual BRF; 2) displayed an abnormally high level of neural synchronisation in the same low-frequency rhythm, indicated by increased relative EEG power; and, 3) the high-α band was found to be positively correlated with both the high-β and low-γ bands. Overall, these abnormalities in cortical oscillations resemble a mild version of TCD, which has been associated with the pathophysiology of various neuropsychiatric disorders including SZ and psychosis Jeanmonod et al, 2003;Llinas et al, 1999;Schulman et al, 2011).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In severe OCD cases, where all other available therapeutic approaches have been tried without success, neurosurgery may be a treatment option. Only unblinded studies are available that showed improvements after Á bilateral anterior capsulotomy (Lippitz et al 1999; Ló pez Ibor and Ló pez-Ibor Aliñ o 1975; Mindus et al 1990Mindus et al , 1999Oliver et al 2003;Rü ck, 2006;Skoog and Skoog 1999), Á cingulotomy (Baer et al 1995;Dougherty et al 2002;Jenike et al 1991a;Kim et al 2003;Richter et al 2004), Á limbic leucotomy (Cumming et al 1995;Hay et al 1993;Montoya et al 2002;Sachdev and Hay 1995), Á subcaudate tractotomy (Hodgkiss et al 1995;Woerdeman et al 2006) or Á thalamotomy/pallidotomy (Jeanmonod et al 2003).…”
Section: Repetitive Transcranial Magnetic Stimulation (Rtms)mentioning
confidence: 99%